Whole transcriptome sequencing reveals neutrophils’ transcriptional landscape associated with active tuberculosis - Geng, Xingzhu; Wu, Xiaolin; Yang, Qianting; Xin, Henan; Zhang, Bin; Wang, Dakuan; Liu, Liguo; Liu, Song; Chen, Qi; Liu, Zisen; Zhang, Mingxia; Pan, Shouguo; et al. (Frontiers in Immunology, 2022)
Neutrophils have been recognized to play an important role in the pathogenesis of tuberculosis in recent years. However, the whole transcriptional profile of neutrophils in association with tuberculosis has not yet been characterized. In this study, we performed global RNA-seq on peripheral blood neutrophils from active tuberculosis patients (ATB, n=15); latent tuberculosis infections (LTBI, n=22); and healthy controls (HC, n=21). The results showed that greater perturbations of gene expression patterns happened in neutrophils from ATB individuals than HC or those with LTBI, and a total of 344 differentially expressed genes (DEGs) were observed. Functional enrichment analysis showed that besides the interferon signaling pathway, multiple pattern recognition receptor pathways were significantly activated in ATB, such as NOD-like receptors and Toll-like receptors. Meanwhile, we also observed that the expression of genes related to endocytosis, secretory granules, and neutrophils degranulation were downregulated. Our data also showed that the NF-κB signaling pathway might be inhibited in patients with ATB, which could increase Mycobacterium tuberculosis survival and lead to active tuberculosis status. Furthermore, we validated the accuracy of some differentially expressed genes in an independent cohort using quantitative PCR, and obtained three novel genes (RBM3, CSRNP1, SRSF5) with the ability to discriminate active tuberculosis from LTBI and HC.